Endoscopic treatment of obesity: A protocol of updated systematic review with network meta-analysis of randomized controlled trials. - Eun Jeong Gong; Chang Seok Bang; Gwang Ho Baik (PLoS ONE)
Background Obesity, characterized by excessive fat accumulation, poses a significant public health challenge globally. Recent advancements in medical technology have heralded the emergence of endoscopic bariatric treatments (EBTs) as innovative alternatives to conventional obesity interventions. Despite previous systematic reviews and network meta-analyses, they also highlighted discrepancies in outcomes and efficacy among different EBTs. Here, we will update a systematic review and network meta-analysis of randomized controlled trials (RCTs) focusing on EBTs and presents a protocol for the reproducibility and transparency. Methods The core protocol of this study was registered at PROSPERO database (CRD42024514249) on Jan 2024. Core databases including MEDLINE through PubMed, Embase, and Cochrane library will be searched relevant studies, and a systematic review with network meta-analysis will be performed. Two evaluators (EJ Gong and CS Bang) will independently screen the titles and abstracts following the eligibility criteria; (1) RCTs investigated the compared the efficacy of EBTs and controls; (2) studies published in English; and (3) studies in full-text format. We will exclude studies meeting the following criteria; (1) studies that did not report the treatment outcomes, such as percent excess weight loss or percent total body weight loss; (2) case reports and review articles; (3) ineligible research objects, for example, animals or children; and (4) insufficient data regarding treatment outcome. The primary outcomes will be the common efficacy metric found after systematic review of relevant studies, such as percent excess weight loss or percent total body weight loss with a follow-up of at least 6 months. Narrative (descriptive) synthesis is planned and quantitative synthesis will be used if the included studies are sufficiently homogenous. The quality of the identified studies will be assessed using the Cochrane Risk of Bias assessment tool version 2.0 (ROB 2.0). All the systematic review and network meta-analysis process will be undertaken keeping the principles of the Preferred Reporting Items for a Systematic Review and Meta-analysis for systematic review protocols (PRISMA-P) and PRISMA Extension Statement for Reporting of Systematic Reviews Incorporating Network Meta-analyses of Health Care Interventions (PRISMA-NMA). Discussion This updated systematic review and network meta-analysis will provide information about comparative efficacy of various EBTs and this will help physicians in the decision-making process for the selection of treatment modalities in the clinical practice.